(untitled) (Bulletin KNOB, 2004)
In the second half of the nineteenth century the mechanized production of building components expanded enormously; there were also drastic innovations in the manufacturing of traditional materials such as brick, mortar, glass, roof tiles and paint materials. Besides, technical progress resulted in the development of a wide range of materials that had never been used before, such as wood cement, concrete, aluminium, asphalt, cast iron, steel and zinc. It is important to make a distinction between on the one hand new materials and on the other hand old materials that were produced or processed in new ways. This split is also to be found in the work of two major architects from the neo-Gothic period, a seemingly very traditional movement. In different ways, Alfred Tepe (1840-1920) and P.J.H. (Pierre) Cuypers (1872-1921) both realised ideals inspired by the Middle Ages in their buildings. It is surprising to see that in spite of their ardour to revive the Middle Ages as accurately as possible, such an enormous difference in their views on use of materials arose. Tepe’s buildings look rather austere because they are almost entirely constructed of brick. Apart from a few, small exceptions Tepe believed in a traditional use of materials. For the saddle roofs he chose a slate covering in a period when roof tiles produced in factories were cheaper. He made the roofs with traditional wood constructions and nearly all his churches have stone (ribbed) vaults. Only in a few places did Tepe opt for a modern material. Although his use of materials is austere, his use of colour is not so at all. Practically all Tepe’s buildings were realised under the guidance of his source of inspiration Gerardus Wilhelmus van Heukelum (1834-1910) of the St Bernulfus guild. The use of natural stone was not avoided from the start, this was only the case later on in the construction of new churches. It seems quite obvious that this is due to the strong influence Van Heukelum had on Tepe. Both gentlemen preferred a pure, honest and Dutch use of materials and Van Heukelum had direct family ties with brick manufacturers in the province of Gelderland. With castle De Haar Cuypers could largely realise his ideal image of a medieval lodge comparable to that of the cathedral of Cologne. Cuypers used a wide variety of materials, either in a very traditional or in a very advanced, modern way. Nearly all the materials introduced in the building industry during the nineteenth century are represented in the castle, ranging from granite, terracotta and natural stone to asphalt, (Monier) concrete and iron constructions. The modern materials and construction methods were especially used in the new parts of the castle, where concrete was left visible and imitation natural stone and modern iron constructions were applied. Although one would not expect it, the historicizing new construction of the medieval castle itself also contains plenty of concrete. The roof of the Hall of castle De Haar is one of the earliest roofs of Monier concrete in the Netherlands. The modern materials were not just used in exceptional situations such as a private and generously financed restoration, but also for churches, such as St Gummus church in the province of Brabant and for public buildings, such as the Rijksmuseum.